Los mayas y los otros: integración y distinción cultural en el paisaje urbano y rural de Copán - Felix Kupprat (Journal de la Société des Américanistes)
Intercultural and interethnic relations within Maya sites have received little attention, despite their relevance for our understanding of urban and social developments during the Classic period. One reason for this is the methodological problem of defining ethnic markers and distinguishing cultural influences from cultural identities. Nevertheless, in some cases, there is sufficient data to trace distinctive collective identities within a site and to infer certain dynamics of population development that had a concrete political impact. This article explores new ways of approaching Maya identity in the regional state of Copan by the means of a comparative epigraphic analysis that responds to settlement patterns and recent archaeological and bioarchaeological data. At this site on the periphery of the Maya world, the sociopolitical authorities developed a cultural identity based on the elite culture of 5th-century Tikal, which was instrumentalized in order to integrate a multi-ethnic population under a hegemonic ideological model.